Sex And Functional Status As A Predictor Of Death Of People Living With HIV/AIDS On Arv Therapy In Buleleng Hospital - Putu Dian Prima Kusuma Dewi; Putu Sukma Megaputri; Ni Ketut Ayu Wulandari; Ni Made Dwi Yunica Astriani; Ari Pertama Watiningsih; Luh Ayu Dianiati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Cases of death in HIV / AIDS are still a benchmark for the success of treatment. Studies of predictors of death in people with HIV in the general population are still very limited. Longitudinal analytic with a retrospective approach using cohort data of patients receiving antiretroviral drugs at Buleleng General Hospital in the period 2006-2015. Analysis uses logistic regression with SPSS version 17. Results show a total of 1204 that the incidence of total mortality rate is 3 per 100 person years. 50% of deaths occurred at 0.14 years of observation. Men and the general functional status of employment were predictors of death in PLHAs. Men have a risk of death 2.12 times higher than that of women (aOR 2.12 (p 0.01 CI 1.28-3.51). Functional status of beds increases the risk of death aOR 2.14 (CI 1.39-3.29 p 0.01).Men have a risk of death evaluation of the success of antiretroviral therapy considers studies and differences in needs between women and men.The functional status of beds shows a poor clinical condition that increases the risk of death in people with HIV. Evaluation of regularity of treatment and the incidence of gender-based deaths should be done more intensively.